Arbuscular mycorrhizal fungi improve the growth and phosphorus uptake of mung bean plants fertilized with composted rock phosphate fed dung in alkaline soil environment. (14th September 2019) - Wahid, Fazli; Sharif, Muhammad; Fahad, Shah; Adnan, Muhammad; Khan, Imtiaz Ali; Aksoy, Emre; Ali, Amjad; Sultan, Tariq; Alam, Mukhtar; Saeed, Muhammad; Ullah, Hidayat; Basir, Abdul; et al.
Abstract: Inoculation effect of arbuscular mycorrhizal fungi (AMF) on phosphorus (P) transfer from composted dung of cattle with a diet supplemented with powdered rock phosphate (RP) and their successive uptake by mung bean plants was assessed in alkaline soil. The efficacy of composted RP fed dung alone or/and in combination with AMF inoculums containing six different species were compared with SSP in six replicates per treatment in pots. The results showed that the association of AMF with composted RP fed dung had a positive effect on mung bean shoot (3.04 g) and root (2.62 g) biomass, chlorophyll (a, b), carotenoid contents and N (58.38 mg plant −1 ) and P (4.61 mg plant −1 ) uptake. Similarly, the percent roots colonization (56%) and nodulation of mung bean plant roots and their post-harvest soil properties were also improved by the inoculation of AMF together with composted RP fed dung. It is concluded that the combined application of AMF with composted RP fed dung has almost the same effect as SSP for improving mung bean plants growth and their nutrients uptake. Moreover, AMF inoculants can be used as a suitable biofertilizer in combination with locally available organic sources of fertilizers for improving P status and growth of plants in alkaline soils.